A study on blood donor characteristics and preferred environment of South Koreans during the COVID-19 pandemic: A conjoint analysis - Kim, Young-Jae; Cho, Jeong-Hyung (Frontiers in Public Health, 2023)
Objective The COVID-19 pandemic has caused a decrease in the number of blood donors worldwide, posing a global problem. Therefore, this study investigates people who have continuously participated in blood donation during the COVID-19 pandemic and collects basic information as a reference for maintaining stable amounts of blood during future pandemics. Methods The participants of this study were selected from the population of South Korea through stratified sampling considering region and age distributions. Owing to the COVID-19 pandemic, the participants were recruited online through Embrain, an online research and survey company, from June 1 to June 28, 2021. Data were collected from a total of 1,043 participants and used in the study. Results The results of this study showed that there was a difference between the donors group and non-donors group in factors such as donation attitude (F = 73.342, p < 0.001), donation knowledge (F = 6.530, p < 0.01), and preventive health behavior (F = 12.352, p < 0.001). Overall, blood donors showed favorable attitude toward and considerable knowledge of blood donation as well as a high level of preventive health behavior. The environment most preferred by people who participated in blood donation during the COVID-19 pandemic was “going with family to a blood donation center that gives out free gifts in a region far away with no confirmed cases,” which showed the highest utility (utility = 0.734). Conclusion Even during pandemics, donation attitude, donation knowledge, and preventive health behavior can serve as key factors affecting participation in blood donation. Additionally, blood donation centers that donors can visit with their families represent a favorable environment for the promotion of blood donation during pandemics.